Numerical study of wings with wavy leading and trailing edges. - Serson, Douglas (2016)
Inspired by the pectoral flippers of the humpback whale, the use of spanwise waviness in wings has been considered in the literature as a possible way of delaying the stall, and possibly also reducing the drag coefficient, allowing for improved aerodynamic characteristics. In order to provide a better understanding of this flow control mechanism, the present work investigates numerically the effect of the waviness on the flow around infinite wings with a NACA0012 profile. The study consists of direct numerical simulations employing the spectral/hp method, which is available through the nektar++ library. Considering the high computational cost of the simulations performed, several improvements were introduced to the method, making it more efficient and allowing higher Reynolds numbers to be analysed. These improvements to the method include a coordinate transformation technique to treat the waviness, changes to the parallelism strategy, and an adaptive polynomial order refinement procedure. Initially, simulations were performed for a very low value of the Reynolds number Re = 1, 000, allowing the three-dimensional flow structures to be observed in de- tail. In this case, the results show that the waviness leads to a decrease in the lift-to-drag ratio, accompanied by a strong reduction in the fluctuations of the lift force. The reduction in the lift-to-drag ratio is the combined effect of lower drag and lift forces, and is associated with a regime where the flow remains attached behind the peaks of the leading edge while there are distinct regions of flow separation behind the troughs. Then, simulations with Re = 10, 000 were considered. For high angles of attack, the results for this case are similar to the lower Re, with the waviness leading to separation behind the troughs and reducing both the lift and the drag. However, for a lower angle of attack the waviness leads to a large increase in the lift coefficient. This was observed to be related to the fact that flow around the straight wing is laminar in this case, with the waviness inducing transition to a turbulent state. Finally, the case Re = 50, 000 was considered, with the results showing a good agreement with experiments presented in the literature.